Low CRIM1 Levels Predict Poor Prognosis in Breast Cancer Patients - Wen, Wei; Jiang, Baohong; Cao, Xi; Xie, Liming; Zhang, Xiaoli; Li, Yuehua; He, Rongfang (Frontiers in Oncology, 2022)
Background: CRIM1 (cysteine-rich transmembrane bone morphogenetic protein regulator 1) influences the development and preservation of the nervous system, capillary development, and vascular maintenance. Although CRIM1 are reported to involved in multiple cancers, its role in breast cancer is unclear. Methods: We investigated CRIM1 expression levels using Oncomine, HPA, and Immunohistochemistry analyses. BC-GenExMiner was employed to evaluate the relationship of CRIM1 expression with the clinicopathological characteristics of breast cancer. Correlation of CRIM1 with tumor immune infiltration was explored via TIMER. Its association with breast cancer prognosis was assessed via Kaplan-Meier analysis and PrognoScan. Gene set enrichment analysis (GSEA) was utilized to determine the cascades that are linked to CRIM1 in breast cancer. Finally, we explored CRIM1 and its co-expressed genes using R (3.6.3). Results: Here, we find that CRIM1 expression is downregulated in various subtypes of breast cancer and that its expression positively correlates with ER (estrogen receptor) and PR (progesterone receptor) levels. However, in breast cancer tissues versus non-malignant tissues, CRIM1 levels negatively correlated with HER-2 (human epidermal growth factor receptor), basal-like status, p53 status, as well as triple-negative status. Notably, CRIM1 expression was positively linked to the level of infiltration by CD8+ T-cells, endothelial cells, and neutrophils. Survival analysis found that low CRIM1 levels correlated with poorer DMFS (distant metastasis-free survival), RFS (relapse-free survival) along with OS (overall survival). Besides, DIXDC1 and PFDN6 were correlated to CRIM1 possibly. Conclusion: Our findings highlight CRIM1 as a possible treatment target or prognostic marker in breast cancer. More research is needed to better understand the prognostic value of CRIM1 in breast cancer.